GUESSTIMATING BODY MASS INDEX (BMI): HOW GOOD ARE WE, REALLY?. (8th June 2013) - Jagun, O; Chan, G; Tee, W J; Ahmed, Z; Brady, S; Elsafty, Z; Martin, H; Buckley, M; Sarwar, S; Smyth, C; Farrell, R
Abstract : Introduction: According to the World Health Organisation definition, the body mass index (BMI) is a simple index of weight-for-height that is commonly used to classify overweight and obesity in adults. Although it has it's limitations it provides the most useful population-level measure of overweight and obesity as it is the same for both sexes and for all ages of adults. Visual estimation of BMI is routinely used in the clinic setting to direct lifestyle advice. Identifying the correct BMI is particularly important in gastroenterology as we frequently manage patients with malabsorption, chronic inflammatory diseases and liver disease. Aims/Background: To evaluate and compare the positive predictive value (PPV), negative predictive value (NPV) sensitivity and specificity of prediction of overweight/obese in gastroenterology patients among doctors and nurses. Also, to assess for individual bias in the physicians making the judgements based on their own BMI calculations. Method: For the purposes of our study, BMI was defined as <18=underweight, 18–24.9=normal, 25–29.9=overweight and >30=obese. All consecutive patients attending the gastroenterology clinic in the month of December 2012 were recruited prospectively. The patients' BMI were measured using Seca weight and height measuring devices in clinic. BMI estimation sheets were distributed to the four junior doctors and the clinic nurse at each clinic over a one-month period. The estimations between the two groups were blinded as to prevent any bias. Results: In total, 80 patients were recruited of which there were 48(60%) males and 32(40%) female patients, mean age 46.4±14.6 years. The mean weight was 77.3±17.0kg and the mean height was 163.9±9.4 cm. The mean BMI was 29.3±4.3 kg/m2 in males and 28.4±6.7 kg/m2 in females, p=0.500. There were 2 (2.5%) patients who were underweight, 19 (23.8%) who had a normal BMI, 24 (30.0%) who were overweight and 35 (43.8%) who were obese. The PPV, NPV, sensitivity and specificity for the prediction of overweight/obese patients were 90.0%, 73.7%, 91.5% and 70.0% respectively for nurses compared to 94.0%, 60.0%, 79.7% and 85.7% for doctors. It was also found that if doctors were of a normal BMI, they were less likely to predict the correct patients' BMI compared to those who were overweight, 44.7% vs 100%, p=0.31. Conclusion: Healthcare professionals were poor at predicting patients' BMI in the setting of gastroenterology outpatients. There was a trend, particularly among doctors to underestimate patients' weight. This trend was more common among doctors who were of a normal BMI. Worryingly, approximately three quarter of our patients are overweight or obese, higher than previously reported prevalence by the department of health. To allow for accurate lifestyle and dietary advice, it is important that all patients have their weight and height measured in clinic.